Higher education systems 3.0 : harnessing systemness, delivering performance - Lane, Jason E.; Johnstone, D. Bruce (Donald Bruce), 1941- (SUNY series, critical Issues in higher education, 2013)
"A comprehensive examination of higher education multi-campus systems and their role in improving state economies and communities"--Provided by publisher.